Estimated Number of People Who Inject Drugs in the United States. (6th July 2022) - Bradley, Heather; Hall, Eric W; Asher, Alice; Furukawa, Nathan W; Jones, Christopher M; Shealey, Jalissa; Buchacz, Kate; Handanagic, Senad; Crepaz, Nicole; Rosenberg, Eli S
Abstract: Background: Public health data signal increases in the number of people who inject drugs (PWID) in the United States during the past decade. An updated PWID population size estimate is critical for informing interventions and policies aiming to reduce injection-associated infections and overdose, as well as to provide a baseline for assessments of pandemic-related changes in injection drug use. Methods: We used a modified multiplier approach to estimate the number of adults who injected drugs in the United States in 2018. We deduced the estimated number of nonfatal overdose events among PWID from 2 of our previously published estimates: the number of injection-involved overdose deaths and the meta-analyzed ratio of nonfatal to fatal overdose. The number of nonfatal overdose events was divided by prevalence of nonfatal overdose among current PWID for a population size estimate. Results: There were an estimated 3 694 500 (95% confidence interval [CI], 1 872 700–7 273 300) PWID in the United States in 2018, representing 1.46% (95% CI, .74–2.87) of the adult population. The estimated prevalence of injection drug use was highest among males (2.1%; 95% CI, 1.1–4.2), non-Hispanic Whites (1.8%; 95% CI, .9–3.6), and adults aged 18–39 years (1.8%; 95% CI, .9–3.6). Conclusions: Using transparent, replicable methods and largely publicly available data, we provide the first update to the number of people who inject drugs in the United States in nearly 10 years. Findings suggest the population size of PWID has substantially grown in the past decade and that prevention services for PWID should be proportionally increased. Abstract : An estimated 3 694 500 people injected drugs in the United States in 2018, more than 5 times the 2011 estimate. This estimate can be used to inform health interventions for people who inject drugs and as a baseline to assess pandemic-attributable changes in substance use.